A kinetic and kinematic comparison of the grab start and track start in swimming - Allen, David (My University, 1997)
Fifteen collegiate swimmers (8 females, mean age = 18.38,7 males, mean age = 19.43) volunteered as subjects to determine differences between 5 kinematic variables and 2 kinetic variables using the grab start and track start. Subjects attended a 1 hour practice session, completing a minimum of 15 starts of each technique. Subjects were videotaped performing 14 trials of each start technique. Force data were collected from the last 5 trials of each technique. A MANOVA revealed the grab start had a significantly (p < .05) longer flight distance for all subjects. Subjects who preferred the grab start achieved 13.1% increase (normalized to body height) in flight distance with the grab start, while subjects preferring the track start had a 9.6% increased flight distance kith the grab start. A significant difference (p < .05) was also found between the preferred starting technique and the absorption force (AFz) in the vertical direction. This force was attributed to the back leg pushing against the block during this time period. Male subjects who preferred the track start had a significantly (p < .05) faster start time for the track start than males who preferred the grab start. No other significant differences were found between any other variables. Further investigations on different populations would allow the results to be more generalized. More practice sessions should also be completed to decrease the effect of learning on the performance of the start techniques.
Keywords: Swimming - Starts and turns